Therapeutic Effect of Huayu Tongluo Moxibustion Combined with Low Frequency Repetitive Transcranial Magnetic Therapy on Patients with Mild to Post-Stroke Depression - SHEN Rong; YUAN Aihong; TANG Youbin; GAO Zhiqun; XIE Hongyu; ZHU Shaoquan; LIU Youxiang (康复学报)
ObjectiveTo observe the effects of Huayu Tongluo moxibustion combined with low frequency repetitive transcranial magnetic stimulation (rTMS) on depression symptoms and severity, neurological deficits and sleep efficiency of patients with mild to moderate post-stroke depression (PSD).MethodsA total of 40 patients with mild to moderate PSD in the First Affiliated Hospital of Anhui University of Traditional Chinese Medicine from January 2022 to October 2023 were randomly divided into control group and observation group, with 20 cases in each group. Both groups received routine treatment and rehabilitation training. The control group received low-frequency rTMS treatment on the basis of routine treatment and rehabilitation training, with a stimulation frequency of 1 Hz, a stimulation intensity of 80% MT, a stimulation time of 10 seconds, an interval time of 2 seconds, and a total of 1000 pulses.The observation group received treatment with Huayu Tongluo moxibustion [pressure moxibustion at Baihui acupoint (GV 20) , suspension moxibustion at Shenting (GV 24) and Dazhui acupoint(GV 14)]on the basis of the control group, once a day, five times a week, lasting for three weeks. Before and after treatment, the Hamilton depression scale (HAMD) score, patient health questionnaire depression scale 9 (PHQ-9) score, and latency and amplitude of event related potential P300 were used to evaluate the symptoms and severity of depression; the national institutes of health stroke scale (NIHSS) score was used to evaluate the degree of neurological deficits; the Pittsburgh sleep quality index (PSQI) was used to evaluate patient sleep efficiency.Results(1) Symptoms and severity of depression: compared with that before treatment, the HAMD and PHQ-9 scores in both groups decreased significantly after treatment, the latency of event related potential P300 decreased significantly and the amplitude of event related potential P300 increased significantly, the differences were statistically significant (P<0.05). Compared with the control group, HAMD and PHQ-9 scores in the observation group after treatment were lower, the latency of event related potential P300 was lower and the amplitude of event related potential P300 was higher, and the differences were statistically significant (P<0.05) . (2)Degree of neurological deficits: compared with that before treatment, NIHSS scores in both groups decreased significantly after treatment (P<0.05). Compared with the control group, NIHSS scores in the observation group was lower after treatment, the difference was statistically significant(P<0.05) . (3)Sleep efficiency: compared with that before treatment, sleep efficiency in both groups increased significantly after treatment, the difference was statistically significant(P<0.05). Compared with the control group, there was no statistically significant difference of sleep efficiency in the observation group after treatment (P>0.05).ConclusionHuayu Tongluo moxibustion combined with low-frequency rTMS can effectively improve depression symptoms, neurological deficits, and sleep efficiency of patients with mild to moderate PSD, which is worthy of clinical promotion and application.